Expression of Melanocortin-1 Receptor and Serum Melanin in Canities at Young Male students - Anggraini, Dwi Rita; Feriyawati, Lita; Sitorus, Mega Sari; Syarifah, Siti; Daulay, Milahayati (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Molecular genetics suggest that hair pigmentation is related to the melanocortin-1 receptor gene. It is a G protein-coupled receptor, which is activated by a number of peptides to stimulate melanogenesis. Melanocortin-1 receptor gene mutation tends to produce functional variability in premature hair graying (PHG) or canities. AIM: Therefore, the objective of this study was to determine melanocortin-1 receptor expression and asses serum melanin in college students canities at Universitas Sumatera Utara. METHODS: This study was a cross-sectional design. We recruited 80 subjects equally divided into normal (control) and premature hair graying groups. The sample included males, aged 25 years who had gray hair and had no history of pigmentary disorders of the skin. Expression of melanocortin-1 receptor was detected with conventional PCR and serum melanin was measured with Elisa using Elisa kit melanin for human. RESULTS: The results showed that the Mean ± SD graying age was 20.28 ± 1.99 years with an age range of 19–24 years and the average age in the control group was 21.25 ± 2.02 years with an age range of 18–24 years. Melanocortin-1 receptor gene expression was shown in the control and PHG groups. Serum melanin levels were decreased significantly (p = 0.0001) in the gray-haired group was 9.27 ± 1.62 μg/dl and the control group was 10.72 ± 1.78 μg/dl. CONCLUSION: Melanocortin-1 receptor gene plays a role in hair graying at young age and there serum melanin levels were low significantly.